Modern aspects of the use of natural polyphenols in tumor prevention and therapy - Galina Sufianova; Ilgiz Gareev; Ozal Beylerli; Jianing Wu; Alina Shumadalova; Albert Sufianov; Albert Sufianov; Xin Chen; Shiguang Zhao; Shiguang Zhao (Frontiers in Cell and Developmental Biology, 2022)
Polyphenols are secondary plant metabolites or organic compounds synthesized by them. In other words, these are molecules that are found in plants. Due to the wide variety of polyphenols and the plants in which they are found, these compounds are divided according to the source of origin, the function of the polyphenols, and their chemical structure; where the main ones are flavonoids. All the beneficial properties of polyphenols have not yet been studied, since this group of substances is very extensive and diverse. However, most polyphenols are known to be powerful antioxidants and have anti-inflammatory effects. Polyphenols help fight cell damage caused by free radicals and immune system components. In particular, polyphenols are credited with a preventive effect that helps protect the body from certain forms of cancer. The onset and progression of tumors may be related directly to oxidative stress, or inflammation. These processes can increase the amount of DNA damage and lead to loss of control over cell division. A number of studies have shown that oxidative stress uncontrolled by antioxidants or an uncontrolled and prolonged inflammatory process increases the risk of developing sarcoma, melanoma, and breast, lung, liver, and prostate cancer. Therefore, a more in-depth study of the effect of polyphenolic compounds on certain signaling pathways that determine the complex cascade of oncogenesis is a promising direction in the search for new methods for the prevention and treatment of tumors.